Did post-enlargement labor mobility help the EU to adjust during the Great Recession? The case of Slovakia - Kahanec, Martin; Mytna Kurokeva, Lucia (Bratislava, 2014)
"This paper evaluates the mobility patterns of Slovaks into the rest of the European Union (EU) following Slovakia’s EU accession in 2004 and through the Great Recession. Combining information from various data sources including the Slovak Labor Force Survey and conducting our own statistical analysis of selectivity into migration, we study whether and how migration responded to asymmetric economic shocks at home and abroad. We identify a number of shifts in the directionality and composition of migration flows in terms of the destinations, gender, age, educational attainment and occupation, reflecting changing labor market conditions in receiving countries and Slovakia. We show that besides the standard demographic factors, migration propensity was higher among the unemployed and from the more depressed regions of Slovakia. We conclude that labor migration has served as an important adjustment mechanism in the country and more generally in the EU labor market."